2022
DOI: 10.1038/s41467-022-31232-4
|View full text |Cite
|
Sign up to set email alerts
|

Complete biosynthetic pathway to the antidiabetic drug acarbose

Abstract: Acarbose is a bacterial-derived α-glucosidase inhibitor clinically used to treat patients with type 2 diabetes. As type 2 diabetes is on the rise worldwide, the market demand for acarbose has also increased. Despite its significant therapeutic importance, how it is made in nature is not completely understood. Here, we report the complete biosynthetic pathway to acarbose and its structural components, GDP-valienol and O-4-amino-(4,6-dideoxy-α-D-glucopyranosyl)-(1→4)-O-α-D-glucopyranosyl-(1→4)-D-glucopyranose. G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 46 publications
0
26
0
Order By: Relevance
“…Although our previous studies showed that acarbose or acarbose-related BGCs are widely distributed in many actinomycetes, the degree to which the gacI -like bifunctional GT-PP gene is distributed among those BGCs was unclear. Therefore, a follow-up study of those BGCs was performed, and the results showed that from 139 strains that harbor acarbose or acarbose-related BGCs, 129 strains have a gacI -type gene, instead of a pair of acbI and acbJ genes, and all of them are strains of Streptomyces .…”
Section: Resultsmentioning
confidence: 94%
See 4 more Smart Citations
“…Although our previous studies showed that acarbose or acarbose-related BGCs are widely distributed in many actinomycetes, the degree to which the gacI -like bifunctional GT-PP gene is distributed among those BGCs was unclear. Therefore, a follow-up study of those BGCs was performed, and the results showed that from 139 strains that harbor acarbose or acarbose-related BGCs, 129 strains have a gacI -type gene, instead of a pair of acbI and acbJ genes, and all of them are strains of Streptomyces .…”
Section: Resultsmentioning
confidence: 94%
“…The results suggest that GacI can effectively dephosphorylate both V7P and V1,7PP but not 1-epi-V1,7PP or Aca7P, which are consistent with the substrate preference of AcbJ from the acarbose pathway in Actinoplanes sp. SE50/110 . Although both V7P and V1,7PP can be effectively dephosphorylated by GacI, the natural substrate for GacI is believed to be V1,7PP, as its dephosphorylation product valienol 1-phosphate (V1P, 9 ) has recently been identified as an intermediate in acarbose biosynthesis (Figure A) .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations